Modelling of the reactor cycle cost for thorium-fuelled PWR and environmental aspects of a nuclear fuel cycle - Oettingen, Mikołaj (Wydawnictwa AGH, 2019)
The paper presents the methodology applied to the cost modelling of the uranium-thorium nuclear reactor cycle for PWR reactors as well as brief introduction to the environmental impact of the nuclear fuel cycle. The reactor core contains seed uranium fuel and blanket thorium fuel. In such a cycle, energy is produced in the fission of $^{235}$U included in the fresh fuel and in the fission of $^{233}$U bread from the fertile $^{232}$Th. A modified methodology developed by the OECD Nuclear Energy Agency was used for the reactor cycle cost modelling. The method is based on the levelized lifetime cost methodology for a reactor cycle, which is directly related to the heavy metal mass balance. Contrary to the case of uranium-fuelled nuclear reactors, the cost modelling includes the additional cash flow for thorium fuel. The abundance of thorium in the Earth’s crust is about 3–5 times larger than that of uranium, which suggests its promising potential as a nuclear fuel. However, this needs to be proved economically.
Geology, Geophysics & Environment
Keywords: thorium; PWR; fuel cycle; levelized costs; environmental impact